INVESTIGATION OF RAPID AND EXTENDED CLAY LANDSLIDES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Results of studies of fast and long clay landslides are presented. Three mechanisms are explained that cause the movement of the geomass of landslides: under the influence of gravity forces, sowing and lubrication of the landslide bed along the base of the guides. It has been found that gravity forces do not move significant geomasses over long distances. Grease is formed by the penetration of rainfall or geochemical transformation of the underlying rock layer during the period of movement of the landslide geomass. The third mechanism consists in participation of nanoparticles of lower layer of moving landslide as natural nanoparticles.
Keywords: landslides, movement mechanisms, gravity, geochemical transformation of underlying rocks, nanoparticles as nanoparticles.